New WHO guidelines for cancer pain in adults and adolescents - A. D. Kaprin; G. R. Abuzarova; D. V. Nevzorova; G. S. Alekseeva; E. V. Gameeva; A. R. Gevorkov; N. M. Bychkova; R. R. Sarmanayeva; S. V. Kuznetcov (Исследования и практика в медицине, 2021)
In this article we performed publication analysis devoted to pain medicine in oncology during anticancer therapy and in palliative setting. Until recently, the main WHO guidelines for pain management in oncology were the recommendations of 1996, which included only pain relievers, as well as adjuvant and symptomatic drugs, which were applied according to the WHO analgesic ladder. These recommendations were based on the collective expert opinion of leading clinicians and scientists. The new WHO clinical guidelines were published in 2019. They are based on the principles of evidence-based medicine, including modern concepts of the etiology and pathogenesis of tumor pain syndrome. This recommendations contain sections on the analgesic efficacy of radiation therapy and antitumor drug therapy. The new WHO recommendations have not yet been published in Russian and are not sufficiently available for a wide range of oncologists and palliative specialists in our country. The purpose of this publication is to present within one volume a concise but complete and comprehensible discussion of the latest trends in pain therapy in oncology, published by WHO experts.